The Adorned Body : Mapping Ancient Maya Dress - Carter, Nicholas (Anthropologist); Houston, Stephen D.; Rossi, Franco (Anthropologist) (Linda Schele series in Maya and pre-Columbian studies., 2020)
"How we dress our bodies--through clothing, footwear, headgear, jewelry, haircuts, and more--is key to the expression of status and identity. This idea was as true for ancient Maya civilization as it is today, yet few studies have centered on what ancient Maya peoples wore and why. In The Adorned Body, Nicholas Carter, Stephen Houston, and Franco Rossi bring together contributions from a wide range of scholars, leading to the first in-depth study of Maya dress in pre-Columbian times.Incorporating artistic, hieroglyphic, and archaeological sources, this book explores the clothing and ornaments of ancient Maya peoples, systematically examining who wore what, deducing the varied purposes and meanings of dress items and larger ensembles, and determining the methods and materials with which such items were created. Each essay investigates a category of dress--including headgear, pendants and necklaces, body painting, footwear, and facial ornaments--and considers the variations within each of these categories, as well as popular styles and trends through time. The final chapters reveal broader views and comparisons about costume ensembles and their social roles. Shedding new light on the art and archaeology of the ancient Americas, The Adorned Body offers a thorough map of Maya dress that will be of interest to scholars and fashion enthusiasts alike."